2022
DOI: 10.1111/1750-3841.16021
|View full text |Cite
|
Sign up to set email alerts
|

Hot air‐assisted radio frequency drying of apricots: Mathematical modeling study for process design

Abstract: Conventional hot air and solar energy processes have been used for apricot. These processes had adverse effects on the quality due to the longer process times, and this indicates the need for an innovative approach. Radio frequency (RF) processing has innovation potential for drying with its volumetric heating feature, but an optimal process should be designed for process efficiency in industrial‐scale applications. Therefore, the objective of this study was to confirm the RF process for industrial‐scale apric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The uneven distribution of temperature significantly affects the moisture distribution and ultimately affects the product quality [ 11 ]. In RF drying experiments, it is difficult to visualize the effects of different factors on the interior of the product, such as electric field, temperature, water concentration, and water vapor concentration [ 12 ]. In addition, experimental approaches have some disadvantages, such as long cycles, high economic cost, low efficiency, and operating difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…The uneven distribution of temperature significantly affects the moisture distribution and ultimately affects the product quality [ 11 ]. In RF drying experiments, it is difficult to visualize the effects of different factors on the interior of the product, such as electric field, temperature, water concentration, and water vapor concentration [ 12 ]. In addition, experimental approaches have some disadvantages, such as long cycles, high economic cost, low efficiency, and operating difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Each dehydration time was 10 min. Final samples were immersed in 100% tert-butanol for 15 min and then placed in a vacuum freeze drying machine for processing [ 22 , 23 , 24 , 25 , 28 , 29 , 30 ]. The sample observation surface was placed upward and fixed on the scanning electron microscopy sample table with conductive tape after treatment, and the surface was coated with an ion sputter-coating instrument for 90 s, then placed under a scanning electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that the total phenol content, shrinkage rate, and color change of bananas after RF treatment at the early stage of hot air drying showed an upward trend [ 26 , 27 ], and the rehydration rate and hardness of samples decreased. Hot air-assisted RF drying was also applied to the drying of apricots [ 28 , 29 ], and the experimental results showed that the drying process had significant effects on the color, antioxidant capacity, and β-carotene content of preserved apricots. In addition, the drying time was significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In drying experiments, it is difficult to visualize the effects of different factors on the product’s interior, such as temperature and moisture concentration [ 14 ]. Additionally, experimental procedures have several drawbacks, including lengthy cycles, high economic costs, poor efficiency, and operational challenges.…”
Section: Introductionmentioning
confidence: 99%